KINERJA TERMAL ARSITEKTUR VERNAKULAR SUKU OSING BERDASARKAN TIPE ATAP - Rizka, Hablana; Defiana, Ima; Noerwasito, V. Totok (Jurnal Arsitektur ARCADE, 2022)
Abstract: The traditional house of the Osing Tribe is one of the various vernacular architectures of East Java. Precisely located in Kemiren Village, Banyuwangi Regency at an altitude of 170 meters above sea level, which is included in the low topography of a humid tropical climate with a very high humidity average of about 85%, and an average temperature of 27 Â° C, so that it can affect the comfort of the building. This house has three unique types of roofs. The three types of roofs include Tikel Balung, Cecorogan, and Baresan. The Osing traditional house developed from community traditions and took advantage of local potential, including existing technology, materials, and knowledge. However, it is not yet known which type of roof is more efficient in its responsiveness to outside air temperature. This study aims to determine the type of roof of the Osing building that can reduce temperature or respond to current air temperature conditions. This study uses the simulation method. The simulation method is used in this study to examine the thermal performance of several types of roofing envelopes using the Design Builder software version 7. The final results of this study indicate that the vernacular house with the Tikel Balung roof type is better able to reduce the temperature or respond to current air temperature conditions than the Tikel Balung roof type in other types of roof models.Abstrak: Rumah adat Suku Osing merupakan salah satu dari berbagai arsitektur vernacular Jawa Timur. Tepatnya terletak di Desa Kemiren Kabupaten Banyuwangi pada ketinggian 170 mdpl yang termasuk dalam topografi rendah beriklim tropis lembab dengan rerarta kelembaban sangat tinggi sekitar 85%, dan rerata suhu 27Â°C sehingga dapat mempengaruhi kenyamanan bangunan. Rumah ini memiliki tiga tipe atap yang unik. Tiga tipe atap tersebut meliputi, Tikel Balung, Cecorogan, dan Baresan. Rumah adat Osing berkembang dari tradisi masyarakat dan memanfaatkan potensi setempat, meliputi teknologi, material, dan pengetahuan yang ada. Namun belum diketahui tipe atap mana yang lebih efisien dalam responsifitasnya terhadap suhu udara luar. Penelitian ini bertujuan untuk mengetahui tipe atap bangunan Osing yang paling mampu menurunkan suhu atau merespon kondisi suhu udara saat ini. Penelitian ini menggunakan metode simulasi. Metode simulasi digunakan pada penelitian ini untuk mengkaji kinerja termal pada beberapa tipe atap selubung bangunan dengan menggunakan software Design Builder versi 7. Hasil akhir dari penelitian ini menunjukkan bahwa rumah vernakular dengan tipe atap Tikel Balung lebih mampu menurunkan suhu atau merespon kondisi suhu udara saat ini dibandingkan tipe model atap lain.